Pediatric imaging cases - Chung, Ellen (New York : Oxford University Press, 2012)
Featuring 150 cases and over 400 high-quality images, this resource offers a complete survey of the field of pediatric radiology. Cases are formatted as questions and answers, allowing for self-assessment, complete with relevant radiologic findings, differential diagnoses, teaching points, further steps in management, and suggested further readings. It offers a comprehensive overview of the clinical issues of pediatric radiology: cardiovascular system, gastrointestinal system, genitourinary system, spine, neuroradiology, chest and airway, and musculoskeletal system.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Pediatric diagnostic imaging -- Case studies